A by‐product from virgin olive oil production (pâté) encapsulated by fluid bed coating: evaluation of the phenolic profile after shelf‐life test and invitro gastrointestinal digestion. (16th May 2021) - Bellumori, Maria; De Marchi, Laura; Mainente, Federica; Zanoni, Francesca; Cecchi, Lorenzo; Innocenti, Marzia; Mulinacci, Nadia; Zoccatelli, Gianni
Abstract: Pâté is a by‐product of virgin olive oil production presenting a high phenolic content and beneficial health effects. This research aims to evaluate the storage stability of phenolic compounds of pâté and a coated formulation, and to verify the bioaccessibility of the phenolic compounds. An accelerated shelf‐life test at 40 °C/75% relative humidity was carried out for 75 days. Different combinations of degradative and hydrolytic reactions impacted the results. Indeed, at the end of the storage period, 84% of phenols was recovered in pâté with free tyrosol and hydroxytyrosol showing an increase due to secoiridoids hydrolysis. The total phenolic content of coated pâté did not significantly decrease, showing a higher increment of free tyrosol and hydroxytyrosol. Simulated digestion led to the liberation of 15% of phenols by both samples. In conclusion, the coating process improved the stability of pâté phenolic compounds without affecting their bioaccessibility. Abstract : Pâté is a by‐product obtained by a new and innovative two‐phase decanting process during olive oil production. This research aims to evaluate the storage stability of phenolic compounds of pâté by an accelerated shelf‐life test and a coated formulation obtained by processing the matrix through fluid bed technology using modified starch and maltodextrin. The evaluation by simulated in vitro digestion of the bioaccessibility of pâté phenolic compounds was also carried out.